Gendered punishment and protest in a context of conflict: strip searching in Northern Ireland - Byrne, Conor (Body Searches and Imprisonment, 2023)
Throughout the period of violent conflict in Northern Ireland, the strip searching of politically affiliated prisoners has met with individual and collective resistance, within prisons and supported by protest in communities. Even after the signing of the Belfast Agreement in 1998, the practice of strip searching has remained contentious within this transitional society. This chapter presents a critical chronology of strip searching in prisons in Northern Ireland. Based on primary research, it starts by exploring the experiences of men who participated in the Republican Blanket Protest, analysing the role and impact of masculinity both for prisoners subject to violent and intrusive methods of searching, as well as for prison officers conducting the searches. Women’s gendered experiences are next examined, from the forcible searching of Republican women in Armagh and Maghaberry prisons, then considering how later searching procedures for all women prisoners in Hydebank Wood were shaped by decades of conflict. Acknowledging strip searching as a form of sexual harm and abuse, the chapter explores how the intersections between conflict, political imprisonment and gender have impacted on prisoners’ experiences of searches and on the ways that the practice has been resisted.